O impacto do Programa Escola de Tempo Integral no desempenho escolar da rede pública do Espírito Santo entre 2015 e 2021 - Amaro, Mateus Valentim (2023)
The “Escola em Tempo Integral’’ program composes the public policies for basic education in Espirito Santo and began to be implemented in 2015. Since then the number of schools covered by this public policy has grown exponentially, from just 1 school in 2015 to 92 schools in 2021. The evaluation of public policies started to gain space especially following State reforms, when concepts such as transparency and accountability became notorious. Impact evaluations are those that seek to answer whether a program achieved the objectives existing in the design of the policy, that is, whether the program worked or not. Having in sight this context that expanded the space for transparency, this dissertation consists of an impact evaluation of the fulltime school program of Espirito Santo, which was established by Law n. 799/2015. To this end, this research is of a quantitative nature and made use of the statistical methods propensity score matching to define the counterfactual, and difference in differences to analyze the data. The sample consisted of a control group and a treatment group. These were represented by schools that participate in the full-time school program, while those were represented by schools that do not participate. The result was that the program did not impact school performance, which was measured by PAEBES. Therefore, the causal hypothesis was rejected. The contributions of this research are theoretical, social, and practical, as it advances the discussion on public educational policies, which is essential for society, in addition to providing tools for public management on the impact of the program and whether it should be continued or not.